The impact of food-hygiene practices, leadership effectiveness, and spiritual intelligence towards Program Latihan Dan Khidmat Negara (PLKN) foodservice performance / Mazni Saad - Saad, Mazni (Institute of Graduate Studies, UiTM, 2017)
Food poisoning cases in the National Service and Training Programme (PLKN) camps are on the rise for over 10 consecutive years despite measures taken by responsible parties and therefore require further attention. Specifically, an unchanged pattern of foodborne incidence has triggered an alarming question on the sustainable operation of food service business in these camps. The objectives of this study are to (i) assess the Food-hygiene Practices of food handlers at PLKN, (ii) to analyse the relationship between Leadership Effectiveness, Food-hygiene Practices, and Spiritual Intelligence (SQ) and (iii) to investigate the impact of these study variables; Leadership Effectiveness, Food-hygiene Practices, and SQ on PLKN”s Foodservice Performance. The existing level of Food-hygiene Practices was assessed through questionnaire, interview, and observation, as well as microbial sampling experiments. The questionnaire also assessed the relationship and impact of the four parameters of the study (Leadership Effectiveness, Food-hygiene Practices, SQ, and Foodservice Performance). The survey yielded 87.80% responses from 81 operating camps in Malaysia and provided 1026 usable datasets. Six sets of interviews were conducted among the supervisory personnel of the PLKN camps. For empirical data, 288 microbiological samplings of food-contact surfaces (FCS) and 36 drinking water sources were conducted. The data was analysed using the partial least square and appropriate statistic tools. The microbial analyses failed to correlate with the cleanliness survey, but were consistent with food poisoning outbreaks in the camps. FCS with flat open surfaces such as cutting boards and food trays were found exposed to secondary contamination during the drying and storing stage…